HYDROPOWER AS THE MAIN SOURCE OF ELECTRICITY IN SOUTHEAST ACEH - Rifkie, M. Akbar; Adi Sastra P Tarigan; Solly Aryza (INFOKUM, 2022)
The use of water energy worldwide has increased in recent years to reduce emissions. This abundant energy source has the potential for electricity production of 75 GW throughout Indonesia. However, its construction requires a lot of time and money, so it has not become the main choice to be a solution to energy needs. In this study, we will observe the process of generating electrical energy in Southeast Aceh Regency whose electricity needs are supplied from the Lawe Sikap PLTM which has only been operating for one year, and the Sepakat PLTMH which has been operating since 1997 to determine the level of efficiency and reliability. By measuring the electrical energy and water discharge available each period by the operator at each power plant during January-February 2022. The results show that the Lawe Sikap PLTM and the Sepakat PLTMH can become the main electricity supports in Southeast Aceh Regency with a percentage of 50-85%.